Impact of uniaxial compressive strain on physical and electronic parameters of a 10 nm germanene nanoribbon field effect transistor. (December 2016) - Bayani, Amir Hossein; Dideban, Daryoosh; Moezi, Negin
Abstract: In this paper, a top-gated Germanene nanoribbon field effect transistor (GeNR-FET) with and without applying a compressive strain is investigated. Three strain strengths ( ε  = 3%, 5% and 10%) are applied to the different regions of the proposed GeNR-FET and the obtained transistor characteristics are compared with each other. Moreover, physical and electronic parameters of unstrained and strained GeNR are calculated. The results indicate that the bandgap and electron effective mass of GeNR increase firstly by increasing the strain strength but then decrease and this behavior affects on the transistor figures of merit. We find that the Ion /Ioff ratio and subthreshold swing (SS) of the unstrained FET improves when a 3% compressive strain is applied to the whole of the device. Also, applying a 10% strain to the device increases the ON current of the FET due to strain-induced self-doping behavior, but the obtained transistor parameters for this structure are not very satisfactory. Next, we apply the compressive strain either only to the channel or only to the source and drain of the devices. The obtained results show, due to high lattice mismatch between the channel and the leads, the transistor performance of the strained FETs are almost the same or even worse than that of the unstrained one. A novel engineered device is proposed and the transistor figures of merit and in particular, the analog performance are emphasized. It is found that the new proposed device has a better Ion /Ioff ratio and SS. In addition, negative differential resistance occurs in this transistor. The analog performance of the novel device is obtained and compared with the unstrained and 3% strained GeNR-FET in the subthreshold region. It is observed that the proposed device has a better transconductance and voltage gain so that it is a good candidate for analog applications. Highlights: We consider a Germanene nanoribbon (GeNR) as a field effect transistor and calculate the physical and electronic parameters of the GeNR with and without applying compressive strain. We build a novel field effect transistor based on strain-induced self-doping behavior in Germanene nanoribbon Dirac-like electronic structure by considering 10% strained source and drain and 3% strained channel. The bandgap and electron effective mass of the GeNR increases and then decreases by increasing strain strength. The transistor properties of the 3% strained GeNR FET is better than the unstrained one's. The novel proposed device based on 10% strained source and drain and 3% strained channel shows negative differential resistance and also has a good analog performance in subthreshold region.